Night of 1000 wolves ebook - Curnow, Bobby (Night of 1000 Wolves (2012)., 2012)
In the Dark Ages, the tranquil life of Harrick Benjyon and his family is shattered by unthinkable tragedy. Before they can react, the family find themselves under siege by hordes of wolves with one aim: Death! A race for survival becomes all the more impossible by the arrival of the supernatural... and the dark secrets that lie at the heart of the Benjyon family.